Incubação de cooperativas populares e extensão universitária : o caso da INCOOP – Incubadora Regional de Cooperativas Populares Universidade Federal de São Carlos - Matsuda, Patricia Mari (Universidade Federal de São Carlos, 2010)
The Technological Incubators of Popular Cooperatives - ITCP represent a solid basis for those excluded from the labor market may to be organize and insert on the market as a socioeconomic order. This dissertation considers the link between the incubators and Universities through the extension activity. The basic hypothesis of this work is that Regional Popular Incubator Cooperatives - INCOOP, establishing a relationship between students and administrative staff at UFSCar with future cooperators, provides socioeconomic benefits (for cooperatives) and academics (for teachers, students and administrative staff UFSCar). It aims to identify the socioeconomic and academics gains obtained, respectively, by the people who get involved with the cooperatives and the teachers and students through a case study. The methodology was based on literature review and case study at INCOOP-UFSCar. As research procedures were used questionnaires and visits to the Incubator. The gotten results show personal and academics gains for teachers, students and technical administrative servers, and also socioeconomics benefits to the cooperators.
Keywords: Cooperativas - organizações; Incubadoras; Economia solidária; Extensão universitária; Cooperação - universidade e sociedade; Technologic incubators of popular cooperatives; Solidary economy; Universitary extension; ENGENHARIAS::ENGENHARIA DE PRODUCAO